Loss of CD96 Expression as a Marker of HIV-Specific CD8+ T-Cell Differentiation and Dysfunction - Bunet, Rémi; Nayrac, Manon; Ramani, Hardik; Sylla, Mohamed; Durand, Madeleine; Chartrand-Lefebvre, Carl; Routy, Jean-Pierre; Landay, Alan L.; Gauchat, Jean-Francois; Chomont, Nicolas; Ancuta, Petronela; Kaufmann, Daniel E.; et al. (Frontiers in Immunology, 2021)
Persistent immune activation and inflammation in people living with HIV (PLWH) are associated with immunosenescence, premature aging and increased risk of non-AIDS comorbidities, with the underlying mechanisms not fully understood. In this study, we show that downregulation of the T-cell immunoglobulin receptor CD96 on CD8+ T-cells from PLWH is associated with decreased expression of the co-stimulatory receptors CD27 and CD28, higher expression of the senescence marker CD57 and accumulation of a terminally differentiated T-cell memory phenotype. In addition, we show that circulating CD96-low CD8+ T-cells display lower proliferative potential compared to their CD96-high counterparts and that loss of CD96 expression by HIV-specific CD8+ T-cells is associated with a suboptimal response to HIV antigens. In conclusion, our results suggest that CD96 marks CD8+ T-cells with competent responses to HIV and the loss of its expression might be used as a biomarker for CD8+ T-cell senescence and dysfunction in PLWH.